Return Migration, Wage Differentials, and the Optimal Migration Duration - Christian Dustmann (Institute for the Study of Labor (IZA), 2001)
In simple static models, migration increases with the wage differential between host and home country. In a dynamic framework, and if migrations are temporary, the size of the migrant population in the host country depends also on the migration duration. This paper analyses optimal migration durations in a model which rationalises the decision of the migrant to return to his home country, despite persistently higher wages in the host country. The analysis shows that, if migrations are temporary, the optimal migration duration may decrease if the wage differential grows larger. Using micro data for Germany, the second part of the paper provides some empirical evidence which is compatible with this hypothesis.
Keywords: D9; F22; 330; Life cycle models; international migration; Migrationstheorie; Dauer; Rückwanderung; Zeitpräferenz; Lebenszyklus; Lohnstruktur; Schätzung; Theorie; Deutschland